2018
DOI: 10.1111/jfpe.12946
|View full text |Cite
|
Sign up to set email alerts
|

Microwave airflow drying of pecans at variable microwave power

Abstract: In this study, the dielectric properties of two varieties of pecan nuts at different moistures (10–30% w.b.), temperatures (25–85°C) were determined and the effect of microwave (MW) power density (0.8–2.6 W/g) and exposure time (30–300 s) on moisture content of pecan were approximated by response surface analysis. According to a comprehensive assessment of these results, phased varying power design for MW‐assisted air drying (PPMAD) was appropriate designed to dry pecan nuts. The result indicated that the pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Ultrasound technology might be a solution to compensate for the disadvantage of the microwave drying. Our previous works have been dedicated to investigate the effect of microwave on dielectric properties (Zhang, Li, Cheng, et al, 2019), drying process kinetics (Zhang, Li, Deng et al, 2019), and pecan's quality (Jigang, Zhien, Jin, Jianghua, & Song, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound technology might be a solution to compensate for the disadvantage of the microwave drying. Our previous works have been dedicated to investigate the effect of microwave on dielectric properties (Zhang, Li, Cheng, et al, 2019), drying process kinetics (Zhang, Li, Deng et al, 2019), and pecan's quality (Jigang, Zhien, Jin, Jianghua, & Song, 2016) .…”
Section: Introductionmentioning
confidence: 99%
“…The full factorial experiment is carried out in accordance with the optimization algorithm using the following operations: planning the full factorial experiment, determining the coefficients of the regression equation, analyzing the significance of the regression coefficients, and the identification of the optimum (Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The most recommended treatment was nut exposure for 2.5 min as it significantly delayed crude protein degradation and lipid decrease compared to the untreated control, in addition to significantly inhibiting moisture loss and increasing the total soluble sugar content, maintaining the sensory quality of the fresh nut throughout the period. Zhang et al (2018) suggested microwave drying, although with variable power in stages, proving to be a promising technique since water loss was effective without affecting the composition of the main nutrients and sensory quality.…”
Section: Discussionmentioning
confidence: 99%